What is the evidence on the policy specifications, development processes and effectiveness of existing front-of-pack food labelling policies in the WHO European Region? - Kelly, Bridget; Jewell, Jo (World Health Organization Regional Office for Europe, 2018)
Interpretive front-of-pack food labelling (FOPL) is a policy priority for promoting healthy diets. Research evidence indicates that consumers have a reasonable understanding of interpretive FOPL systems and their understanding improves with label familiarity and consistency within the market. A government-endorsed interpretive FOPL policy was found in 15 Member States of the WHO European Region, and this report summarizes the evidence on their development and implementation to support policy-makers in navigating these processes. Most existing policies have been implemented under voluntary arrangements, with variable penetration into the marketplace. Policy development that is led by government and based on formative research, and that engages stakeholders and the public, is most likely to lead to acceptable, credible and effective policies. FOPL implementation is best supported by policy provisions that encourage widespread uptake of the system and allow for formal evaluation of both implementation and impact.
Health Evidence Network synthesis report, ISSN 2227-4316 61
Keywords: Consumer Behavior; zemědělství a potravinářství; podpora zdraví; Health Promotion; Food Preferences; Food; Food Labeling; Program Evaluation; zákonodárství potravinářské; Psychology; hodnocení programu; psychologie; chování spotřebitelů; zdravá strava; Legislation, Food; označování potravin; Diet, Healthy; potraviny; preference v jídle